2021
DOI: 10.1186/s12951-021-01133-7
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxypropylmethylcellulose as a film and hydrogel carrier for ACP nanoprecursors to deliver biomimetic mineralization

Abstract: Demineralization of hard tooth tissues leads to dental caries, which cause health problems and economic burdens throughout the world. A biomimetic mineralization strategy is expected to reverse early dental caries. Commercially available anti-carious mineralizing products lead to inconclusive clinical results because they cannot continuously replenish the required calcium and phosphate resources. Herein, we prepared a mineralizing film consisting of hydroxypropylmethylcellulose (HPMC) and polyaspartic acid-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Hydroxypropyl methylcellulose (HPMC) has been reported to be applied as a film and hydrogel carrier for polyaspartic acid-stabilized amorphous calcium phosphate (PAsp–ACP) nanoprecursors to deliver biomimetic mineralization of dentin. The hydrogel induced the early mineralization of demineralized dentin after 24 h, with increasing mineralization of the whole demineralized dentin (3–4 μm) after 72–96 h. 171 In another similar study, notoginsenoside R1 (NGR1) was also loaded in Gel–MA as pulp-capping materials to induce dentin formation. 172 Thus, hydrogels have the ability to induce dentin or dentin-like layer mineralization and thickening, helping promote reparative dentinogenesis.…”
Section: Dentin–pulp Complex Regenerative Engineeringmentioning
confidence: 96%
“…Hydroxypropyl methylcellulose (HPMC) has been reported to be applied as a film and hydrogel carrier for polyaspartic acid-stabilized amorphous calcium phosphate (PAsp–ACP) nanoprecursors to deliver biomimetic mineralization of dentin. The hydrogel induced the early mineralization of demineralized dentin after 24 h, with increasing mineralization of the whole demineralized dentin (3–4 μm) after 72–96 h. 171 In another similar study, notoginsenoside R1 (NGR1) was also loaded in Gel–MA as pulp-capping materials to induce dentin formation. 172 Thus, hydrogels have the ability to induce dentin or dentin-like layer mineralization and thickening, helping promote reparative dentinogenesis.…”
Section: Dentin–pulp Complex Regenerative Engineeringmentioning
confidence: 96%
“… Adding polymers to stabilize ACP: Apart from natural biomacromolecules, some synthetic polymers have been shown to slow the rate of ACP aggregation into HAP crystals. Wang et al stabilized ACP with hydroxypropyl methylcellulose and polyaspartic acid, and obtained ordered HAP crystals both in vivo and in vitro, achieving a satisfactory remineralization effect on enamel [ 84 ]. …”
Section: Considerations For the Use Of Hydrogels In Enamel Reminerali...mentioning
confidence: 99%
“…The results show that HPMC’s hydroxyl and methoxy groups can assist the stability of PAsp–ACP nanoparticles and maintain their biomimetic mineralization activity. The results further showed that the biostimulation mineralized membrane induced early mineralization of demineralized dentin after 24 h, and the entire demineralized dentin (3–4 µm) mineralization increased after 72 to 96 h [ 118 ].…”
Section: Application Of Hydrogel In Hard Tissue Regeneration Of Teethmentioning
confidence: 99%